The modern learning ecosystem : a new L&D mindset for the ever-changing workplace - Dillon, JD (ATD Press, 2022)
How can we possibly keep up? This question is front and center in today's workplace thanks to the downright ridiculous pace of change. There's a never-ending stream of new processes, regulations, products, and technologies with which employees must contend. And in the middle of everything--between executives, stakeholders, managers, IT, subject matter experts, legal, and employees--sits L&D, charged with making sure people have the knowledge and skills needed to execute but rarely provided with the time and resources to get it done. The Modern Learning Ecosystem outlines a practical approach for navigating nonstop workplace change. Inspired by decades of operations and talent development experience with the world's most dynamic companies, learning and enablement expert JD Dillon challenges the traditional L&D mindset with a tried-and-true framework that makes right-fit support a meaningful part of the everyday workflow. This book provides step-by-step instructions for architecting a disruption-ready learning ecosystem that will help employees solve today's biggest problems while building the knowledge and skills needed to seize tomorrow's opportunities. Do you believe workplace learning is about more than courses? Do you struggle to gain stakeholder buy-in for alternative learning strategies? Do you want to make smarter decisions when it comes to solution design, technology application and measurement practices? Grab your copy of The Modern Learning Ecosystem and make sure the people you support are always ready for what comes next.